Trans-bronchial lung cryobiopsy in patients at high-risk of complications - Bondue, Benjamin; Schlossmacher, Pascal; Allou, Nathalie; Gazaille, Virgile; Taton, Olivier; Gevenois, Pierre Alain; Vandergheynst, Frederic; Remmelink, Myriam; Leduc, Dimitri (BMC pulmonary medicine, 2021)
The surgical lung biopsy (SLB) is the recommended sampling technique when the pathological analysis of the lung is required in the work-up of an interstitial lung disease (ILD) but trans-bronchial lung cryobiopsy (TBLC) is increasingly recognized as an alternative approach. As TBLCs have lower mortality and morbidity risks than SLB, this study aimed to investigate the safety of TBLCs in patients at higher risk of complications and for whom SLB was not considered as an alternative. This prospective study was conducted in two hospitals in which TBLCs were performed in patients with body mass index (BMI) > 35, and/or older than 75 years, and/or with severely impaired lung function (FVC < 50% or DLCO < 30%), and/or systolic pulmonary artery pressure > 45 mmHg, and/or a clinically significant cardiac disease. Patients with any of these risk factors constituted the high-risk group. Clinical outcomes were compared with those obtained in patients without these risk factors (low-risk group). Ninety-six patients were included between April 2015 and April 2020, respectively 38 and 58 in the high-risk or the low-risk group. No statistically significant difference was observed between both groups in terms of severity and rate of bleeding, pneumothorax, or duration of hospital stay (p value ranging from 0.419 to 0.914). This preliminary study on a limited number of patients suggests that TBLC appears safe in those in whom lung biopsy is at high-risk of complications according to their age, BMI, lung impairment, and cardiac comorbidities.